Transfer of Training-Training Basics - Garavaglia, Paul (Association for Talent Development, 1995)
This issue covers two approaches to training: far transfer and near transfer; it offers a transfer design and a transfer matrix model;it discusses how to ensure transfer of training is successful by using the transfer maintenance system; and reviews how, why, when, and who should measure the transfer of training.